166k views
5 votes
Complete the square for the equation 3x2 - 5x = 2

User Sandwood
by
4.5k points

2 Answers

4 votes

3

2

5

=

2

3x^{2}-5x=2

3x2−5x=2

Factor

1

Move terms to the left side

3

2

5

=

2

3x^{2}-5x=2

3x2−5x=2

3

2

5

2

=

0

3x^{2}-5x-2=0

3x2−5x−2=0

2

Use the sum-product pattern

3

2

5

2

=

0

3x^{2}{\color{#c92786}{-5x}}-2=0

3x2−5x−2=0

3

2

+

6

2

=

0

3x^{2}+{\color{#c92786}{x}}{\color{#c92786}{-6x}}-2=0

3x2+x−6x−2=0

3

Common factor from the two pairs

(

3

2

+

)

+

(

6

2

)

=

0

(3x^{2}+x)+(-6x-2)=0

(3x2+x)+(−6x−2)=0

(

3

+

1

)

2

(

3

+

1

)

=

0

User Sony Kadavan
by
5.5k points
2 votes

Answer:

4/5

Step-by-step explanation:

See image below:)

Complete the square for the equation 3x2 - 5x = 2-example-1
User Dr Ganjoo
by
5.3k points